Vibration control of an energy regenerative seat suspension with variable external resistance. (June 2018) - Ning, Donghong; Sun, Shuaishuai; Du, Haiping; Li, Weihua; Zhang, Nong
Highlights: An electromagnetic damper is proposed, which is energy saving and regenerative. This semi-active actuator system is applied in the seat suspension for vibration control. An experiment is conducted to validate the effectiveness of vibration control. Abstract: In this paper, an energy regenerative seat suspension with a variable external resistance is proposed and built, and a semi-active controller for its vibration control is also designed and validated. The energy regenerative seat suspension is built with a three-phase generator and a gear reducer, which are installed in the scissors structure centre of the seat suspension, and the vibration energy is directly harvested from the rotary movement of suspension's scissors structure. The electromagnetic torque of the semi-active seat suspension actuator is controlled by an external variable resistor. An integrated model including the seat suspension's kinematics and the generator is built and proven to match the test result very well. A simplified experimental phenomenon model is also built based on the test results for the controller design. A state feedback H ∞ controller is proposed for the regenerative seat suspension's semi-active vibration control. The proposed regenerative seat suspension and its controller are validated with both simulations and experiments. A well-tuned passive seat suspension is applied to evaluate the regenerative seat's performance. Based on ISO 2631-1, the frequency-weighted root mean square (FW-RMS) acceleration of the proposed seat suspension has a 22.84% reduction when compared with the passive one, which indicates the improvement of ride comfort. At the same time, the generated RMS power is 1.21 W. The proposed regenerative seat suspension can greatly improve the driver's ride comfort and has the potential to be developed to a self-powered semi-active system.